Penerapan Helmholtz Resonator dan Air Blower Pada Karburator Skep Venturi Untuk Mengurangi Emisi Gas Buang Motor Honda - B. G. Tentua (Industrial Engineering Study Program, Pattimura University, 2015)
Rapid economic progress to encourage the increasing transport demand, on the other hand the natural environment that supports the livelihood of human beings increasingly threatened the quality, so that the negative effects of air pollution on human life is increasingly growing. Experimental research conducted by varying the motor rotation, to measure exhaust emissions on the motorcyle, by applying a Helmholtz resonator and the air blower in the carburator skep ventury . Measurement results showed that the concentration of exhaust emissions standard carburetor produce CO gas amounted to 2255.8 ppm, NO 29 ppm and 28 ppm SO2. whereas the application of Air Blower and the Helmholtz resonator, exhaust emissions decreased, whereas levels of CO gas emissions amounted to 2478.2 ppm and 16 ppm NO and SO2 shows a slight increase of 28.2 ppm.